1994
DOI: 10.1007/bf00190569
|View full text |Cite
|
Sign up to set email alerts
|

Expression of insulin-like growth factor II by a gastric carcinoma associated with hypoglycaemia

Abstract: A gastric cancer with liver metastases was associated with low morning levels of plasma glucose (24 mg/dl), insulin (< 2.5 microU/ml) and growth hormone (0.23 ng/ml). Primary and metastatic tumour tissue stained positively with anti-insulin-like growth factor II (IGF-II) monoclonal antibody. Western immunoblot analysis revealed a high molecular weight IGF-II in the serum: 15 kDa (normal: 7.5 kDa). Postmortem reverse transcription polymerase chain reaction on mRNA from both sites revealed 471 base pairs size cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…An increased proportion of these higher molecular weight IGF-II forms has been reported in plasma and tissue extracts from patients with non-islet cell tumour hypoglycaemia (NICTH), a syndrome resulting from IGF-II overproduction by mesenchymal tumours of nonpancreatic origin (Daughaday et al 1988, Daughaday & Kapadia 1989). More recent reports have shown that IGF-II overexpression and pro-IGF-II forms are more widespread than first thought in various cancers (Horiuchi et al 1994, Singer et al 1995, Hodzic et al 1997, Van der Ven et al 1997).…”
Section: Introductionmentioning
confidence: 96%
“…An increased proportion of these higher molecular weight IGF-II forms has been reported in plasma and tissue extracts from patients with non-islet cell tumour hypoglycaemia (NICTH), a syndrome resulting from IGF-II overproduction by mesenchymal tumours of nonpancreatic origin (Daughaday et al 1988, Daughaday & Kapadia 1989). More recent reports have shown that IGF-II overexpression and pro-IGF-II forms are more widespread than first thought in various cancers (Horiuchi et al 1994, Singer et al 1995, Hodzic et al 1997, Van der Ven et al 1997).…”
Section: Introductionmentioning
confidence: 96%
“…A single subcutaneous injection of recombinant human IGF also can reduce blood potassium in short-term (15). In NICTH, however, hypokalemia was not generally recognized as a clinical symptom (6). In the present case, the reduction of blood potassium was closely related to the development of hypoglycemia.…”
Section: Figure 1 Advanced Liver Metastases By Abdominal Computed Tomentioning
confidence: 44%
“…Non-islet cell tumor hypoglycemia (NICTH) is a rare cause of hypoglycemia, and it is most commonly associated with large, slowgrowing, mesenchymal tumors located in the retroperitoneum or the thorax (2). Hypoglycemia associated with gastric cancer is rarely noted (3)(4)(5)(6), but its clinical manifestations remain to be explored. Here, we report a case of gastric cancer that first presented with hypokalemia, and subsequently developed uncontrollable hypoglycemia in association with multiple liver metastases.…”
Section: Introductionmentioning
confidence: 99%
“…Previous reports on IGF-2 concentrations in blood serum (31,41,49,58) and in tumour extracts (41,58) have demonstrated HMW forms of the IGF-2 peptide, similar to our findings. The demonstration of IGF-2 immunoreactive cells in NICTH cases (25,32,52) and of IGF-2 mRNA expression in tumour tissue extracts, as shown by Northern blots (16,17,25,52), gives further support to the idea of an actual synthesis of this IGF-2 peptide by the neoplastic cells. Our in situ hybridization results, and those in a recent report (1996) by Sohda & Yun (47), using the same technique, offer an additional piece of evidence for such a conclusion.…”
Section: Nicth Pathogenesismentioning
confidence: 78%